MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN MODEL PEMBELAJARAN MELALUI WORKSHOP DI SD NEGERI 009 SEBERANG TELUK KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Herlina Herlina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research was motivated by the low competence of teachers in developing learning models. This researchwas conducted at SD Negeri 009 Seberang Teluk. This study uses school action research (PTS) which consists oftwo cycles. The results of the study indicate that the readiness of teachers to attend workshops in the first cyclehas not met the criteria for success in all aspects, with the achievement of success has not been achieved. In thesecond cycle, the readiness of teachers to attend the workshop has met the criteria of success for all aspects withthe categories already achieved. But it has not been fully achieved one hundred percent. The results of theteacher competency assessment in preparing the learning model in cycle I, get an average score of 65 teacherswith C qualifications with enough categories. After the second cycle, the average value of the teacher in thelearning model is 88 with a qualification of A with a very good category. Based on the results of the researchthat has been carried out it can be concluded that through workshops can improve teacher competency in thelearning model in SD Negeri 009 Seberang Teluk.